Ultrastrong plasmon-phonon coupling via epsilon-near-zero nanocavities - Yoo, Daehan; León-Pérez, Fernando de; Pelton, Matthew; Lee, In-Ho; Mohr, Daniel A.; Raschke, Markus B.; Caldwell, Joshua D.; Martín-Moreno, Luis; Oh, Sang-Hyun (Springer Nature, 2020)
Vibrational ultrastrong coupling, where the light–matter coupling strength is comparable to the vibrational frequency of molecules, presents new opportunities to probe the interactions between molecules and zero-point fluctuations, harness cavity-modified chemical reactions and develop novel devices in the mid-infrared spectral range. Here we use epsilon-near-zero nanocavities filled with a model polar medium (SiO2) to demonstrate ultrastrong coupling between phonons and gap plasmons. We present classical and quantum-mechanical models to quantitatively describe the observed plasmon–phonon ultrastrong coupling phenomena and demonstrate a modal splitting of up to 50% of the resonant frequency (normalized coupling strength η > 0.25). Our wafer-scale nanocavity platform will enable a broad range of vibrational transitions to be harnessed for ultrastrong coupling applications.